Securitization and aggregate investment efficiency - Afrasiab Mirza; Eric Stephens (University of Birmingham, Birmingham Business School, 2016)
This paper studies the welfare properties of competitive equilibria in an economy with incomplete markets subject to idiosyncratic and aggregate shocks. We focus on the role of securitization, whereby borrowers can reduce idiosyncratic asset risk, which enables increased leverage and investment. In the absence of frictions in the securitization process, we show that the ability to securitize assets completes markets. When there are frictions in the market for securitized assets, requiring originators to hold some skin-in-the-game, markets remain incomplete and risk-sharing is limited. In this case, fire-sales are required to repay debt and finance new investments when the economy is hit by a negative shock. Moreover, the equilibrium may be constrained inefficient due to the existence of a pecuniary externality that can result in over or under-investment. We examine policies to correct over-investment and find that a leverage ratio restriction generates a Pareto improvement, while forcing originators to hold additional skin-in-the-game reduces welfare. Both policies reduce leverage and raise prices in a fire-sale, however tightening skin-in-the-game also directly reduces the resources available to those who most need them, which dominates the positive effect of higher prices.
Keywords: D52; D53; E44; G18; G23; 330; Securitization; pecuniary externalities; collateral constraints; financial frictions; macroprudential regulation; re-sales; incomplete markets